EFEKTIVITAS MODEL PEMBELAJARAN BERBASIS MASALAH BERBANTUAN VIDEO MICROLEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA - Afifah Fitri Anindya; Nurina Hidayah (INSPIRAMATIKA, 2026)
This study was motivated by the low level of students’ mathematical critical thinking skills, as indicated by the results of PISA, TIMSS, and observations conducted at SMA Negeri 2 Pekalongan. One effort to address this problem is through the implementation of a Problem-Based Learning model assisted by microlearning videos. This study aimed to determine the effectiveness of the Problem-Based Learning model assisted by microlearning videos on students’ mathematical critical thinking skills in terms of KKTP mastery and the differences in the average mathematical critical thinking skills compared to conventional learning. This study employed a quantitative approach using an experimental method with a Posttest Only Control Group Design. The population consisted of eleventh-grade students of SMA Negeri 2 Pekalongan in the 2024/2025 academic year. The samples were selected using the Cluster Random Sampling technique. Data were collected through observation, interviews, and an essay test consisting of four questions on the coefficient of determination material based on Facione’s critical thinking indicators, namely interpretation, analysis, evaluation, and inference. Data analysis was conducted using the proportion test (z-test) and the mean difference test (t-test). The results showed that more than 70% of students in the experimental class achieved scores above the KKTP (>70). In addition, the t-test results indicated that the average mathematical critical thinking skills of students in the experimental class were higher than those in the control class. Therefore, the Problem-Based Learning model assisted by microlearning videos was effective in improving students’ mathematical critical thinking skills. Keywords:Problem-Based Learning, Microlearning video, mathematical critical thinking.